On strong-coupling correlation functions of circular Wilson loops and local operators - Alday, L; Tseytlin, A (2011)
Motivated by the problem of understanding 3-point correlation functions of gauge-invariant operators in N = 4 super YangMills theory we consider correlators involving Wilson loops and a light operator with fixed quantum numbers. At leading order in the strong-coupling expansion such correlators are given by the light vertex operator evaluated on a semiclassical stringworld surface ending on the corresponding loops at the boundary of AdS 5 × S 5. We study in detail the example of a correlator of two concentric circular Wilson loops and a dilaton vertex operator. The resulting expression is given by an integral of combinations of elliptic functions and can be computed analytically in some special limits.We also consider a generalization of the minimal surface ending on two circles to the case of non-zero angular momentum J in S 5 and discuss a special limit when one of the Wilson loops is effectively replaced by a heavy operator with charge J. © 2011 IOP Publishing Ltd.